Konsep Keseimbangan Ekonomi Pada Mekanisme Pasar dan Penetapan Harga dalam Perspektif Ibnu Khaldun - nur rahmawati (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2019)
AbstractUnstable price fluctuations in the market have an impact on the crisis, in these conditions the government is required to present. But the presence of the government is not only the main way to out from the crisis, because the presence of the government is only one of four factors that can influence the functioning of the market mechanism. One of Islamic thinker who has an idea of market mechanisms and price fixing is Ibn Khaldun. One of his books that studies market mechanisms is the Muqoddimah. In the book of MuqaddimahIbn Khaldun wrote a special chapter discusses the mechanism of prices on the market, that chapter is titled â€œthe prices in the cityâ€.This article studies about Ibn Khaldun's Islamic Economic Thought, especially about market mechanisms and pricing in Islam. After analyzed, the authors conclude that according to Ibn Khaldun there are four factors that influence the process of the market mechanism: 1). Price Theory 2). Value Theory 3). Work Specialization 4). Country. While the price determination of Ibn Khaldun argues: 1). The government are not advised to intervene the market price, because it will have an impact on the market price instability. 2). Regarding to the Supply and Demand, Ibnu Khaldun argued that: The supply of staples for a big cities residents is much greater than the supply of staples for small cities residents. As for demand, Ibn Khaldun said: â€œIf a city develops and its population increases, so people will prosper, then it will cause an increase in demand for goods, and consequently the prices will riseâ€.Â Key Word: Economic Balance, Market Mechanisms, Pricing and Ibn Khaldun